2021
DOI: 10.1097/md.0000000000026675
|View full text |Cite
|
Sign up to set email alerts
|

A survey of PM2.5 preventive behavioral intention and related factors among community elderly in Northern Taiwan

Abstract: Population aging and air pollution are global concerns. The purpose of this study is to explore the relationship among particulate matter with a diameter of 2.5 μm or less (PM2.5) knowledge, PM2.5 preventive attitude, and PM2.5 preventive behavioral intention in the elderly.A cross-sectional survey design was applied in this study, including usage intention and snowball sampling. A total of 617 elderly people aged over 65 participated, and the collected data were quantitatively analyzed.The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The first section collected general demographic information about the participants, covering variables such as geographic area of residence, gender, age, body mass index (BMI), education level, occupation, underlying diseases, allergies, frequency of annual health check-ups, years of experience as VHVs, primary language, household size, monthly family income, perceived adequacy of family income, and local air pollution issues. The inclusion of these particular factors was informed by prior academic research [ 13 , 17 , 22 - 24 , 26 , 27 ], which ensured their relevance to the context of this study and contributed to its overall validity and applicability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first section collected general demographic information about the participants, covering variables such as geographic area of residence, gender, age, body mass index (BMI), education level, occupation, underlying diseases, allergies, frequency of annual health check-ups, years of experience as VHVs, primary language, household size, monthly family income, perceived adequacy of family income, and local air pollution issues. The inclusion of these particular factors was informed by prior academic research [ 13 , 17 , 22 - 24 , 26 , 27 ], which ensured their relevance to the context of this study and contributed to its overall validity and applicability.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in various countries have thoroughly investigated PM 2.5 health literacy assessments at both the national level and within specific populations, employing research tools designed to meet their respective objectives [ 17 , 22 - 25 ]. Several factors have been identified as key determinants influencing different aspects of EHL; however, not all factors have shown significant correlations [ 13 , 17 , 22 - 24 , 26 , 27 ]. EHL has the potential to enable VHVs to lead community environmental management efforts, enhancing awareness and promoting effective collaboration [ 13 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Weng et al [ 46 ] found no difference in PM2.5 knowledge, PM2.5 preventive attitudes, or PM2.5 preventive behavioral intentions among elderly individuals with or without chronic diseases. Additionally, according to Kim et al [ 3 ], knowledge has no impact on personal adaptation behavior against PM:…”
Section: Theory and Hypothesesmentioning
confidence: 99%